PREVENTION AND MANAGEMENT OF OSTEOPOROSIS IN WOMEN - Finch, Cheryl (2015)
Postmenopausal osteoporosis (Type 1) frequently occurs in women in the top 15 and 20 years of menopause. Osteoporosis is a disease characterized by the skeletal system microarchitectural deterioration of bone tissue with increased fragility. This leads to an increased risk of fracture, which can occur even in the absence of intense trauma.